New records of Black Fungus Gnats (Diptera: Sciaridae) from New Caledonia, with the description of two new Bradysia species and an updated checklist - Köhler, Arne; Menzel, Frank (Zootaxa, 2013)
The black fungus gnats Bradysia similigibbosa sp. n. and B. irwini sp. n. are described and new records of species of Bradysia Winnertz, Ctenosciara Tuomikoski, Epidapus Haliday, Pseudolycoriella Menzel & Mohrig, and Scatopsciara Edwards are presented for New Caledonia. A checklist of the sciarids of New Caledonia is given.